Model Based Engineering and Product Line Engineering: Combining Two Powerful Approaches at Raytheon. Issue 2 (21st August 2019) - Young, Bobbi; Clements, Paul
ABSTRACT: Model‐based engineering (MBE) refers to a systems engineering approach that employs models as an integral part of a system's engineering stream, providing a formality and semantic rigor that lends itself to analysis and prediction, thus enabling earlier detection of problems. Product line engineering (PLE) is a way to engineer a portfolio of related products in an efficient manner, taking full advantage of the products' similarities while respecting and managing their differences. Raytheon, one of the world's largest defense contractors, is applying PLE and MBE together and combining the benefits of each. This paper will show how Raytheon is using the two methodologies to support each other, and the lessons it is learning as it does so.